2019
DOI: 10.30638/eemj.2019.154
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo Simulation Method for Risk Management in Road Pavement Maintenance Projects

Abstract: Road pavement management and maintenance are responsible for a considerable amount of resources and energy consumption, with limited options to forecast due to the fact that projects have different sizes, are taking place in regions with various types of soil, landforms or types of distress. The objective of this paper is to offer a solution for risk management using Monte Carlo simulation by taking into consideration three key aspects for the management of any project: costs, time, quality and the most import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Compared with the [15] finding, the research found that the project has a probability of 99.46% to provide benefits. Furthermore, it has been encountered that the importance of the initial budget agrees with the results of [16]. Moreover, it has been discovered that an inverse relationship between maintenance costs and the project's NPV is like the findings of [21].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Compared with the [15] finding, the research found that the project has a probability of 99.46% to provide benefits. Furthermore, it has been encountered that the importance of the initial budget agrees with the results of [16]. Moreover, it has been discovered that an inverse relationship between maintenance costs and the project's NPV is like the findings of [21].…”
Section: Discussionsupporting
confidence: 61%
“…Internationally, the Monte Carlo analysis has been employed in road building and transport management. For instance, one study applied the Monte Carlo simulation in a set of road maintenance projects that found that costs were crucial to keeping the project sustainable [16].…”
Section: Previous Studiesmentioning
confidence: 99%